2019
DOI: 10.1155/2019/8642628
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Dipstick for the Detection of Urinary Tract Infection

Abstract: Background The balance between the choices of UTI diagnostic tools in most primary care settings has been settled for by the more rapid, less labour-intensive dipstick. This study aimed to evaluate the effectiveness of dipstick for diagnosing UTI. Method A total of 429 urine samples were collected from patients suspected of UTI; cultured on cysteine-lactose-electrolyte-deficient (CLED) agar, blood agar, and MacConkey agar; and incubated at 37°C overnight. Urine cultures with bacteria count ≥105 cfu/ml were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
2
15
1
2
Order By: Relevance
“…One of the most prevalent illnesses studied in various clinical settings is urinary tract infection (UTI), which is mostly caused by bacteria, notably Enterobacteriaceae [1]. One of the most common illnesses in people and a common bacterial infection are urinary tract infections (UTIs).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most prevalent illnesses studied in various clinical settings is urinary tract infection (UTI), which is mostly caused by bacteria, notably Enterobacteriaceae [1]. One of the most common illnesses in people and a common bacterial infection are urinary tract infections (UTIs).…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative urine routine suggested that 8 patients were positive for nitrite, and 5 of them had positive urine culture for Escherichia coli. Since Enterobacteriaceae can convert nitrate to nitrite [20], the possibility of E. coli infection is higher in patients with positive preoperative nitrite and requires vigilance.…”
Section: Discussionmentioning
confidence: 99%
“…Clean catch midstream urine was obtained from the patients to avoid contamination. The collected specimens were directly sent to the microbiology laboratory, which inoculated them on blood and MacConkey plates and incubated at 37 о C for 24 hours 9 .…”
Section: Specimens' Collectionmentioning
confidence: 99%